The Athlete-Student Dilemma: Exploring the Experiences of Specially Admitted Student–Athletes at a Division III University - Sean Patrick Hendricks; Ane Turner Johnson (Journal of Applied Sports Management, 2016)
In higher education, it is the responsibility of institutional leaders to ensure the success of all students (Tinto, 1993), even those who failed to meet general admission requirements. This case study explored the challenges associated with enrolling student–athletes at a Division III institution with less than desirable admission standards (Stake, 1995). This study examined 199 specially admitted student–athletes that enrolled at Rowan University between 2007 and 2011 and found that a lack of support and proper programming has placed this population in a disadvantageous position. This coupled with student engagement that was found to further isolate student–athletes from the rest of campus, have contributed to a lack of academic success from many in this population. To better serve the needs of this population, Rowan University could implement a support program to assist this group as it navigates its educational pathways. This support program would include hiring professionals to track and mentor this population as it transitions from high school to college-level academics. Additionally, the institution could increase communication between the athletic department and advising center to better serve the academic needs of this population.
Keywords: Division III athletics; student engagement; specially admitted student-athletes